GEOGRAPHICAL ANALYSIS OF THE FINANCIAL PERFORMANCE OF ACCOMMODATION FACILITIES IN SLOVAKIA: REGIONAL DIFFERENCES AND STABILITY INDICATORS - Jozef LUKÁČ; Peter GALLO; Zuzana KUDLOVÁ (Geo Journal of Tourism and Geosites)
This study explores the geographical analysis of the financial performance of accommodation facilities in Slovakia, focusing on regional differences and stability indicators. The increasing interest in understanding how geographical factors and location affect the financial stability and performance of these facilities provides the backdrop for this research. The aim is to analyze and identify key financial indicators that contribute to the stability of accommodation facilities in various regions of Slovakia and to determine how these indicators differ regionally. To achieve this, the study employs a combination of descriptive statistics, analysis of variance (ANOVA), and clustering methods (k-means). Financial data from 405 accommodation facilities were analyzed, focusing on indicators such as assets, equity, profit, revenue, return o n equity (ROE), and EBITDA. The ANOVA method was used to test the statistical significance of regional differences in these financial metrics, while k-means clustering helped group firms based on their financial stability. The results reveal significant regional disparities in financial performance. Regions like Bratislava and Žilina host larger, more profitable companies, whereas regions such as Prešov and Košice exhibit higher financial risks and negative equity. The study identifies the debt-toequity ratio and EBITDA as crucial indicators of financial stability, highlighting their variability across regions. These findings offer valuable insights for investors and managers in the hospitality industry, aiding in strategic decision -making regarding the placement and management of accommodation facilities.